Parental Adjustment Scale: Validation of a brief, five-item measure of parental adjustment for use with families of typically developing children and children with developmental and/or intellectual disabilities in Australia. (September 2022) - Kelly, Eliza; Day, Jamin J.; Hodges, Julie; Tellegen, Cassandra L.; Ma, Tianyi; Sanders, Matthew R.; Tonge, Bruce; Einfeld, Stewart; Sofronoff, Kate; Gray, Kylie M.; Mazzucchelli, Trevor G.; ,
Abstract: Background: Explores the validity of the five-item parental adjustment scale, a subscale of the previously validated Parenting and Family Adjustment Scales. Aim: The aim was to assess the factor structure and convergent validity of a measure of parental adjustment within parents of typically developing children and parents of childiren with developmental and/or intellectual disabilities. Methods and procedures: Cross-sectional survey data was analysed from Australian parents of children aged 2-12 years who were typically developing children ( N = 683) and had developmental and/or intellectual disabilities ( N = 756). Confirmatory factor analyses and multi-group structural equation modelling examined if the factor structure performed similarly across the two populations. Convergent validity was assessed. Outcomes and results: The confirmatory factor analysis supported the hypothesised one-factor structure for the parental adjustment scale in both populations. Partial measurement invariance confirmed that the scale was structurally consistent within both parent groups. The convergent validity was supported by significant correlations with the DASS-21 in the disability population and the K10 in the typically developing population. Conclusions and implications: This brief, easily administered, five-item scale demonstrates strong potential in assessing parental adjustment, within both parents of typically developing children and parents of children with developmental and/or intellectual disabilities. Highlights: Validation of a five-item, brief measure of parental adjustment (PAS). Multigroup Confirmatory Factor Analysis established measurement invariance of PAS. Validity established with parents of typically developing children and children with disability. Potential for use as a valid quick measure of parental adjustment across settings.